2018
DOI: 10.1177/0044118x18756491
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Combat Bullying: Parental Responses to Bullies, Bystanders, and Victims

Abstract: Despite numerous studies on the topic of bullying, there remains a dearth of information on how parents respond to bullying and the extent to which they are aware of their child's bullying experiences. Using qualitative data from 54 parents in a southeastern state, we explore advice that parents give their children about how to respond when their child is a bullying victim and a bystander in a bullying incident and how fearful parents are of their child being a victim of bullying and reasons behind their fear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…Moreover, our study showed that teachers experienced difficulties in finding agreement with parents on handling bullying situations. Previous research has shown that parents sometimes have different views on what bullying constitutes (Stives, May, Pilkinton, Bethel, & Eakin, 2019). Our findings substantiate this and indicate that finding a solution for a bullying situation together with the parents is certainly not self-evident.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, our study showed that teachers experienced difficulties in finding agreement with parents on handling bullying situations. Previous research has shown that parents sometimes have different views on what bullying constitutes (Stives, May, Pilkinton, Bethel, & Eakin, 2019). Our findings substantiate this and indicate that finding a solution for a bullying situation together with the parents is certainly not self-evident.…”
Section: Discussionsupporting
confidence: 86%
“…Although the effects of parental coaching in response to peer victimization are not yet understood, an emerging literature has begun to document the specific types of advice that parents most commonly provide in response to peer victimization, as well as the other ways in which parents attempt to reduce peer victimization directly. The most common coping strategies suggested by parents include tell an adult, ignore it, be assertive, and retaliate (Cooper & Nickerson, 2013; Harcourt et al, 2015; Harcourt, Jasperse, & Green, 2014; Offrey & Rinaldi, 2017; Sawyer, Mishna, Pepler, & Wiener, 2011; Stives, May, Pilkinton, Bethel, & Eakin, 2019). Parents also report conferring with school personnel about their child’s bullying experiences and talking to the parents of children who bully (Lindstrom Johnson, Waasdorp, Gaias, & Bradshaw, 2019).…”
Section: Addressing Peer Victimization Head-on: Direct Prpvmentioning
confidence: 99%
“…Nevertheless, limited research has addressed whether parents are fearful of their child being bullied. In the only previous study of parental fear of bullying of which we are aware, Stives et al (2019) assessed the extent to which parents were fearful of their child becoming a victim of bullying. In Stives et al's (2019) study of 54 parents, they found parents were evenly divided on whether they were fearful of their child becoming a victim.…”
Section: Why Bullying Happensmentioning
confidence: 99%
“…Parents who were not fearful for their child offered three main reasons; the size of the school, their belief that there was no bullying at their child's school, and their confidence in their child's ability to handle bullying situations on their own. When parents did express fear of victimization, concerns were related to the belief their child was different based on particular characteristics or appearance (Stives et al, 2019).…”
Section: Why Bullying Happensmentioning
confidence: 99%
See 1 more Smart Citation